PERANAN KEGIATAN FINGER PAINTING TERHADAP PERKEMBANGAN SENI RUPA DAN KREATIVITAS ANAK USIA DINI - Ramdini, Tiara Prima; Mayar, Farida (Jurnal Pendidikan Tambusai, 2019)
Early childhood is a child who is in the golden age that must develop various potential with a variety of activities so that all aspects of development develop optimally. All children have the potential and artistry within themselves which are usually done with ordinary drawing activities and are sometimes afraid to explore. Therefore the author is interested in raising a title about the Role of Finger Painting Activities Against the Development of Fine Arts and Early Childhood Creativity. This writing aims to describe the role of finger painting activities on the development of fine arts and children's creativity.